2022
DOI: 10.1038/s41467-022-29469-0
|View full text |Cite
|
Sign up to set email alerts
|

CHMP2A regulates tumor sensitivity to natural killer cell-mediated cytotoxicity

Abstract: Natural killer (NK) cells are known to mediate killing of various cancer types, but tumor cells can develop resistance mechanisms to escape NK cell-mediated killing. Here, we use a “two cell type” whole genome CRISPR-Cas9 screening system to discover key regulators of tumor sensitivity and resistance to NK cell-mediated cytotoxicity in human glioblastoma stem cells (GSC). We identify CHMP2A as a regulator of GSC resistance to NK cell-mediated cytotoxicity and we confirm these findings in a head and neck squamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 78 publications
1
38
0
Order By: Relevance
“…Therefore, the PRG prognostic signature incorporating these two genes could be used to stratify LUAD patients into different risk groups and guide individualized treatment decisions. Previous literature identified that it has been proposed that CHMP2A, a subunit of endosomal sorting complexes required for transport III (ESCRT-III), may help enhance the effect of NK cells on tumor cells ( Bernareggi et al, 2022 ). The data demonstrates that CHMP2A and extracellular vesicles released by tumors can induce programmed cell death in NK cells, thereby diminishing their capacity to efficiently eliminate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the PRG prognostic signature incorporating these two genes could be used to stratify LUAD patients into different risk groups and guide individualized treatment decisions. Previous literature identified that it has been proposed that CHMP2A, a subunit of endosomal sorting complexes required for transport III (ESCRT-III), may help enhance the effect of NK cells on tumor cells ( Bernareggi et al, 2022 ). The data demonstrates that CHMP2A and extracellular vesicles released by tumors can induce programmed cell death in NK cells, thereby diminishing their capacity to efficiently eliminate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…CHMP2A mediates tumor resistance to NK cells by the secretion of extracellular vesicles (EVs) expressing MHC class I chain‐related protein A and B as well as TRAIL. Loss of CHMP2A activates NF‐κB in tumor cells and increases chemokine secretion (CXCL10 and CXCL12), which promotes the recruitment of NK cells to tumors 123 (Figure 2A).…”
Section: Potential Targets Modulating Tumor Immune Responsementioning
confidence: 99%
“…One‐way tumor cells evade NK cell recognition through the loss of expression of various ligands activating NK cells including NK cell receptor DNAM‐1 ligand CD155 [54] and non‐MHC ligand CD48 [56]. Consistent with inhibitory effect of MHC‐I on NK cells, various in vitro CRISPR screens have confirmed the loss of antigen presentation (HLA‐A/B/C/E, TAP1, and TAP2) and interferon‐γ‐signaling pathways (IFNγR2, JAK2, and STAT1) enhance NK cells induced killing [57–59]. Although inhibiting IFNγ sounds like an attractive strategy [51,53], the application should proceed with caution as IFNγ loss can promote tumor immune evasion from CD8+ T cells [34].…”
Section: Application Of Crispr Screens For Immunotherapy Target Disco...mentioning
confidence: 99%